ARAH DAN PERKEMBANGAN PARADIGMA PENELITIAN AKUNTANSI KEUANGAN DAN MANAJEMEN KEUANGAN BERBASIS PASAR MODAL - Prasetyo, Whedy (Jurnal Keuangan dan Perbankan, 2013)
Research paradigm of financial accounting and financial management based on capital market could be dividedinto five focus research areas, they were: market efficiency, economic consequences, income (earning) asa capital market research variable, accounting Information content except profit, and methodology. It wasbased on Ball and Brown research (1968), which focused on the relationship of accounting earnings informationon stock values.The purpose of this article was to describe research paradigm of financial accounting andfinancial management which used the same information based on the capital market. Therefore this articledescribed capital market variables that focused on five variables; market efficiency, economic consequences,earning as a capital market research variable, accounting information content except profit, and methodology. Theexistence of these variables would explain the accounting practices used as the basis in the capital market.